The Relationship Between Anthropometric Measurements and Low-Density Lipoprotein (LDL) Levels in Women Aged 30-50 Years - Harahap, Shofiah Rahmah; Thristy, Isra (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract: Nutritional status is known to influence low-density lipoprotein (LDL) levels. It can be assessed by measuring body mass index (BMI), waist circumference (WC), and mid-upper arm circumference (MUAC). Individuals with obesity are at greater risk of having elevated LDL levels compared to those with normal nutritional status. In women, hormonal changes, particularly during menopause, can affect lipid metabolism and contribute to higher LDL levels. This study aimed to examine the correlation between BMI, WC, and MUAC with LDL levels in women aged 30-50 years. This descriptive-analytical study used a cross-sectional design involving 38 females’ subjects aged 30-50 years old. Anthropometric measurements and LDL levels were recorded. Pearson’s correlation test was used for data analysis. The results showed a weak but statistically significant positive correlation between BMI and LDL (p = 0,034, r = 0,344), WC and LDL (p= 0,035, r=0,344), and MUAC and LDL (p = 0,046, r = 0,326). This study found a correlation between BMI, WC, and MUAC on LDL levels.